Ciências sociais e saúde: um estudo da controvérsia em torno do uso de drogas na psiquiatria - Santos, Ronaldo Bispo dos [UNIFESP] (2016)
This dissertation seeks to understand the controversies surrounding the scientific debate concerning the use of drugs in psychiatry. From a debate on the subject, published in a scientific journal involving two study groups of the Department of Psychiatry of the Federal University of São Paulo, we propose a study on the production of knowledge and truth about users and drugs use, taking these two groups as reference. Having the difference as the object, the research sought to understand which were the foundations that scientifically justified different truth sand which were the criteria used by each Study Group to formulate its proposals for diagnosis and treatment. And along with that, we tried to describe the terminology representing each proposal that allows the definition of its scientific position in the psychiatric field. Based on the scientific publications of each group, it was also possible to find different understandings on the relation health / disease, through which each one, asserting its elfin the competitive struggle for truth, produces its own discourse. Finally, it was possible to identify another materiality of these speeches, since they are among the main discourses that inform public policy concerning treatment programs for drug users at the federal, state and municipal levels.